Memupuk Karakter Tanggung Jawab Sosial Anak Usia 10-12 Tahun Melalui Pemainan Tradisional - Lavinia Dwi Astuti; Gregorius Ari Nugrahanta (Jayapangus Press, 2023)
Moral crisis such as violence, brawl, damage the environmental, vandalism and lack of concern for the environment showed the low character of social responsibility in children. Various ways have been tried to deal with this problem, one of which is cultivated character from an early age. The purpose of this study was to develop a social responsibility character education guidebook based on traditional games for children aged 10-12 years. This study used the ADDIE Research and Development method involving 10 certified teachers, 10 validators, and 8 children aged 10-12 years. The results of the study stated that 1) a traditional game-based social responsibility character guidebook for children aged 10-12 years was developed based on the ADDIE steps. 2) through expert judgment by the validator, this manual was classified as excellent with a recommend of no revision with an average of 3.81. 3) the implementation of the guidebook influences the character of social responsibility for children aged 10-12 years. This is evidenced by the acquisition of the final self-assessment score (M = 3.7500, SE = 0.07319) higher than the initial self-assessment score (M = 2.0875, SE = 0.14447) which is clearly seen at t (7) = 9.435 and the difference is significant, p = 0.000 (p <0.05). H0 is rejected. The magnitude of the effect is classified as a large effect, the percentage of 92% and 85.59% on the N-gain score test is included in the high effectiveness category. Thus, traditional game guidebooks could be said to be effective in developing socially responsible characters.